Stories of innovation for the millennial generation : the Lynceus long view - Formica, Piero (New York, NY : Palgrave Macmillan, 2013)
'The potential of storytelling as a research tool for enhancing the understanding of knowledge creation, acquisition and conversion into innovation and innovative business activities is the methodological underpinning of this book's narrative approach. The subtitle comes from Lynceus, one of the Argonauts who accompanied Jason to Colchis in his quest to find the Golden Fleece, who was said to have excellent sight. Among the various interpretations of the meaning of the Fleece, one version highlights the importance of discovery to innovation by voyaging to'terrae incognitae' (unknown lands). This book is a narrative of a fictional voyage to the'terra incognita' of Innoland - the island of innovation and other mental travels that make sense of events and actions which spur innovation.Stories of Innovation for the Millennial Generation is written for Millennials willing to assimilate and grow dynamic, innovation-driven capabilities which lead to the creation of high-impact startups'--
Includes bibliographical references (pages 146-149).
Keywords: Technological innovations; Creative ability in business; Generation Y